From Karma to Moksha - I K Watson (Journal of Dharma, 1977)
The relation between action (karma) and liberation (moksha) from the bondage of unsatisfactoriness is often so unclear that some have even criticized, either the possibility or the point of the latter, on the ground that it precludes the former. I want in this paper to clarify this relation by showing, firstly, how Karma-yoga can be practised as a means to achieving moksha, and secondly, how that, once achieved, purposive action among us’ in this world remains not only possible for the then Perfected One (siddha), but also in a certain form wholly to be expected.